Dyrektywa pozytywnej prewencji ogólnej — wybrane problemy. Uwagi na tle kodeksu karnego - Kania, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
This article presents basic reservations concerning the prescriptive status of general prevention. Concerns reported in this respect are related not only to its formulation in the act, but also to its substantive meaning. In the light of the findings, it is concluded that the sense of general preventive effect is already sufficiently reflected in the statutory penalty. Therefore, it would be right to add that the “needs to develop legal awareness in society” Art. 53§1 of Penal Code referred to in the Code at the jurisdictional stage are satisfied by the very moment of passing a sentence, which de facto confirms a certain penal reaction provided for in the Code. Therefore, it should be concluded that even the total omission of the general prevention assumptions — expressis verbis — in the current codification would not exclude their presence in the process of rational sentencing.
Keywords: orzecznictwo sądowe; dyrektywa o ogólnej prewencji; kształtowanie świadomości prawnej społeczeństwa